A community-based study of clients' lived experiences of going through the rural HIV care continuum. Issue 1 (2nd January 2021) - Owens, Christopher; Voorheis, Eva; Struble, Nicole; Lester, Jessica N.; Green, Harold D.; Herbenick, Debby; Hubach, Randolph D.; Dodge, Brian
Abstract: This community-based study explored the lived experiences of being in and going through the rural HIV care continuum among 15 gay and bisexual men (GBM) with HIV who live in a rural area of a Midwestern state. Our analysis adapted a six-step interpretative phenomenological analysis. Five themes emerged that reflected the five continuum stages: 1) Diagnosis means death, 2) Linkage to care means uncertainty, 3) HIV care improves the quality of life lost pre- or peri-diagnosis, 4) ART implies life, and 5) Undetectable addresses the medical but not social aspects of HIV. Participants recalled they faced and continue to face social determinants, stigma, and chronic and mental health conditions. Findings provide future research directions and practical implications to address social determinants of health, promote chronic and mental health, and reduce interpersonal stigma throughout all HIV care continuum stages.